SOSIALISASI PERAN TEKNOLOGI MESIN SPRAYER KEPADA PETANI GUNA MENDUKUNG SWASEMBADA PANGAN - suteja suteja; Nasmi Herlina Sari; Sujita Sujita; Rudy Sutanto; Ida Bagus Alit; Syarif Hidayatullah; Ahmad Akromul Huda (Jurnal Agro Dedikasi Masyarakat (JADM), 2026)
Community service program (PKM) aimed at raising awareness of the role of sprayer technology among the Sinar Harapan Farmers’ Group in Setanggor Village, Central Lombok Regency, has been successfully implemented. This PKM activity aims to improve the community’s understanding and ability to apply sprayer technology. The PKM was implemented in four stages: activity preparation, including identification and inventory; implementation of the PKM through outreach and practical training; and finally, evaluation and program sustainability. The results of this PKM indicate that the community is able to understand and apply sprayer technology to improve the efficiency of the rice spraying process for farmers. The results of the pre-test and post-test also showed a significant improvement, indicating that the partners—the Sinar Harapan farmer group in Setanggor Village, Central Lombok Regency—understand and are able to implement rice sprayer technology to achieve food self-sufficiency.